COMPARISON OF RESULTS OF PARLIAMENTARY ELECTIONS 2012-2019 IN UKRAINE - Зінченко, М. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2019)
The results of 2012, 2014, 2019 Ukrainian parliamentary elections which were conducted under the same parallel electoral system, are analyzed. The composition of the Verkhovna Rada of the 7th, 8th and 9th convocation by gender is compared, the possibility of participating in electoral races and being elected by both men and women is analyzed. The number of women and men who were selected by the proportional and majoritarian component of the electoral system is compared. The party composition of each convocation is examined. According to the 2012 elections, 450 people’s deputies were elected, while only 423 people were elected during 2014 and 2019 elections. This is due to Russian aggression in Crimea and eastern Ukraine, which makes it impossible to hold elections in majoritarian constituencies of the indicated regions. With regard to the gender composition of the Parliament, the smallest number of women were represented in the 7th convocation of the Verkhovna Rada of Ukraine, while the largest number was represented in the 9th convocation. This tendency is explained by raising public awareness and greater involvement of women in politics every year, because even with the constancy of the electoral system, the number of women in the Verkhovna Rada of Ukraine has doubled. The majoritarian component of the parallel electoral system remains inaccessible to women, because twice as many women deputies get their seats by proportional component. The political composition of the Ukrainian Parliament changes during each election campaign. Only one political party has been able to overcome the 5 percent electoral barrier in all three of its last campaigns - the All-Ukrainian Motherland Association. Another party has been able to go to parliament twice - the Petro Poroshenko bloc / European Solidarity. All other 11 parties are represented in parliament with only one cadence. A characteristic feature of all three campaigns is the support for a large part of the population of the presidential parties, both in a proportional system and in a majority one, which testifies, however, to the significant influence of the political preferences of the population rather than the influence of the electoral system. The fact that parliament is renewed by more than two-thirds during each of the three election campaigns refutes the argument that MPs or parties do not change and that a new electoral system is required to update parliament.